2019
DOI: 10.3390/w11071491
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of a Northeast Mediterranean Island to Soil Loss. Can Grazing Management Mitigate Erosion?

Abstract: Grazing management practices can be erosion abatement actions for lowering soil loss and the subsequent sediment pollution of surface water bodies. Process-based Geographic Information Systems models provide the opportunity to identify critical areas and hence better target such actions across the landscape. This study implemented the SWAT (Soil Water Assessment Tool) hydrologic and catchment management model to estimate the soil loss vulnerability of the nearly pristine but highly erodible Greek island of Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Even more of a challenge derives from a recent plan of an international industrial conglomerate, supported by the Greek national administration to establish an industrial wind park (39 windmills) on the top of Saos mountain, in the centre of the area destined for Natura 2000, to produce electricity for export. Such a wind park would be visible from far and completely disrupt the ecotouristically most attractive virgin mountain area, dry out headwater springs and streams and require, for the transport of infrastructure and hundreds of tons of concrete, a new road in very steep terrain up from the seaside to the mountain tops -thus creating a new source of major erosion [37]. The municipal council has unanimously opposed this plan, the regional authority too, but future is open.…”
Section: Discussion: On the Chances For A Sustainable Future Of The Imentioning
confidence: 99%
See 3 more Smart Citations
“…Even more of a challenge derives from a recent plan of an international industrial conglomerate, supported by the Greek national administration to establish an industrial wind park (39 windmills) on the top of Saos mountain, in the centre of the area destined for Natura 2000, to produce electricity for export. Such a wind park would be visible from far and completely disrupt the ecotouristically most attractive virgin mountain area, dry out headwater springs and streams and require, for the transport of infrastructure and hundreds of tons of concrete, a new road in very steep terrain up from the seaside to the mountain tops -thus creating a new source of major erosion [37]. The municipal council has unanimously opposed this plan, the regional authority too, but future is open.…”
Section: Discussion: On the Chances For A Sustainable Future Of The Imentioning
confidence: 99%
“…This derives from tectonically deformed bedrock, steep slopes, and restricted groundwater aquifers creating flash floods. Recent research results [37] showed that soil loss under the present situation of animal grazing was 15.8 t/ha, with most vulnerable being an area extending from the center of the island to the adjacent steep headwater areas of its streams. The simulation of a non-grazing scenario resulted in a soil loss diminishing by 25%, indicating that overgrazing alone cannot explain the high erosion rates of the island.…”
Section: The Terrestrial Ecosystem and The Agricultural Sector (Livesmentioning
confidence: 97%
See 2 more Smart Citations
“…Two catastrophic flood events in the summer of 2017 [92], less than a year before our survey, were attributed by several respondents to "erosion" caused and/or aggravated by overgrazing. Additionally, the issue of overgrazing has occupied visiting researchers and environmentalists working on Samothraki for over a decade [57,58,93,94] and these efforts have promoted local discourse aiming at conservation and restoration initiatives on this subject in recent years [64]. It has been shown in other protected areas in Greece that the provision of information to local inhabitants significantly influences perceptions on conservation issues [95].…”
Section: Perceived Anthropogenic Pressures and Threatsmentioning
confidence: 99%